Efektivitas Konsentrasi Sorbitol dalam Medium Purifikasi dalam Menghasilkan Jumlah Sel Viabel pada Isolasi Sel Mesofil Daun Pegagan (Centella asiatica (L.) Urban). - I, Ika Puspitasari; Haryanti, Sri; Prihastanti, Erma (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2006)
Research abaut used sorbitol on purification media for sum cell viable product and effective sorbitol consentration to highes sum viable cell isolation phase pegagan mesophyl cell. Randomized Complete Design with 6 treatmen and 4 block. Sorbitol consentration in purification media was treatmen 0 g/L, 25 g?L, 50 g/L, 75 g/L, 100 g/L and 125 g/L. Parameter was sum of total cell, sum of viabel cell and cell viability. The result of this experiment indicated that the sorbitol in purification media gave the significant effect on the sum cell viabel and cell viability. Effective sorbitol consentration was 25 g/L with obtain sum cell 13,19 x 107 cell/ml and cell viability 99,39%.